Tracheostomy care knowledge and practice among nurses: insight from a tertiary hospital in Northern Tanzania - Msele, Angela N.; Chussi, Desderius C.; Magwizi, Marco R.; Kayuza, Michael P.; Lyimo, Jesca G.; Mtenga, Philbert P.; Mlay, Kenneth J. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2025)
Background: Tracheostomy, a well-established life-saving procedure, is commonly performed worldwide on patients requiring prolonged mechanical ventilation. Adverse events following tracheostomy are not rare and significantly impact patients’ outcomes. Global estimates suggest that inadequate tracheostomy care leads to the death of between 10 and 60% of patients annually. The quality of nursing care after the procedure is crucial in determining patient outcome. From local settings, there is an observed increase in complications and mortality attributed to insufficient knowledge and suboptimal practice of tracheostomy care; however, the current gaps in knowledge and practice have not been systematically documented. This study aims to explore nurses’ level of knowledge and practice of tracheostomy care and its associated factors. Methods: An eight-month analytical cross-sectional study was conducted at Kilimanjaro Christian Medical Centre, where the ear, nose, and throat ward, medical, pediatric, and surgical intensive care units were the specified study units. Data collection tools were structured questionnaires and observation checklists. Descriptive and inferential statistics were utilized in data analysis. Results: Among 52 enrolled nurses, 75% had moderate knowledge, 13.5% had poor knowledge, and 11.5% had good knowledge. 75% of nurses had unsatisfactory practice, and 25% had satisfactory practice. Working units significantly influence nurses’ knowledge level and practice. Conclusions: Knowledge and practice regarding tracheostomy care among nurses is limited. The development of standardized tracheostomy care guidelines, in-service continuous education, and the implementation of a comprehensive tracheostomy care training program are highly recommended to improve proficiency.